A Thematic Analysis on Children's Rights in the Qur'an and Their Impact on Emotional Well-Being - Aulia, Firza Nada; Thobroni, Ahmad Yusam; Safira, Annisa Ilmi (Universitas Muhammadiyah Surakarta, 2025)
The increasing number of cases involving violations of children's human rights indicates that the principles of child protection have not been fully implemented in society. Understanding and internalizing children's human rights is crucial and must be embraced by all parties, including families, educational institutions, and broader communities. This understanding is vital to creating a safe and nurturing environment that supports the optimal growth and development of children, while simultaneously preventing acts of violence, neglect, and exploitation. This article aims to explore the interpretation of Qur'anic verses related to the rights of children and analyze the implications of fulfilling these rights on their emotional well-being. Although children's human rights are not mentioned explicitly in the Qur'an, the essential values and principles concerning their rights are implicitly conveyed across various verses. This study uses a literature-based, descriptive-analytical method and applies a thematic approach by collecting relevant verses under a unified theme to construct a comprehensive conceptual framework. The findings suggest that fulfilling children's rights in light of the Qur'anic teachings has significant implications for their emotional well-being. First, the right to life (QS. Al-An'am: 151) contributes to children's sense of safety and protection, fostering happiness. Second, the right to sustenance (QS. Al-Baqarah: 233) and the right to education (QS. At-Tahrim: 6) enhance children's feelings of being valued and supported, thereby promoting optimism. Third, the right to kind treatment (QS. Ali 'Imran: 159) supports the development of empathy and interpersonal skills. Fourth, the right to express opinions (QS. Ash-Shaffat: 102) nurtures critical thinking, confidence, and a sense of responsibility.